Changes and significance of gut microbiota in children with focal epilepsy before and after treatment - Zhou, Changci; Gong, Shuaizheng; Xiang, Shiting; Liang, Lijuan; Hu, Xia; Huang, Ruiwen; Liao, Zhenyu; Ma, Ye; Xiao, Zhenghui; Qiu, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To clarify the difference of gut microbiota in children with epilepsy before and after treatment, and identify gut microbiota’s possible role in relation to epilepsy occurrence, development and outcome. Methods: 10 untreated children with newly diagnosed focal epilepsy from April, 2020 to October, 2020 were selected and recieved 3-month treatment with oxcarbazepine. The case group was then divided into pre-treatment subgroup and post-treatment subgroup. 14 healthy children of the same age group were recruited as control group. Fecal samples from children in both the case and control groups were collected. The community of gut microbiota was analyzed by 16s ribosomal DNA sequencing. Metastas analysis and LEfSe analysis were used to identify different bacteria between and within groups. Results: There were significant differences in α diversity among the 3 groups. Besides, the differences in gut microbiota composition in 3 groups were identified by principal co-ordinates analysis (PCoA) based on Bray-Curtis distance, which showed similar composition of the pre-treatment and post-treatment subgroups. For the phyla level, relative abundance of Actinobacteria in the pre-treatment subgroup was significantly higher than that in the control group, which decreased significantly after 3 months of treatment and showed no significant difference between the control group. In terms of the genus level, Parabacteroides, Escherichia/Shigella, Streptococcus, Romboutsia, Collinsella and Megamonas in the pre-treatment subgroup were enriched, while Faecalibacterium was enriched in the control group. After 3-month treatment, the relative abundance of Escherichia/Shigella, Streptococcus, Romboutsia, Collinsella and Megamonas reduced obviously. Despite some significantly different genera between the post-treatment subgroup and control group, the number of these genera decreased. Conclusion: Faecalibacterium were associated with protection against focal epilepsy, while Collinsella, Escherichia/Shigella, Streptococcus and Megamonas were associated with promotion for epilepsy. Besides, there were significant differences in microbial community before and after treatment, and gut microbiota of those with effective treatment changed to healthy children, indicating that therapeutic effect may be related to the changes of gut microbiota.